THE EFFECT OF CHEMOTHERAPY ON THE CONDITION OF THE ORAL CAVITY - Руденка, Альона (SWorldJournal, 2026)
Chemotherapy remains one of the leading methods of cancer treatment, but its systemic cytotoxic effects often lead to a wide range of side effects, including significant damage to the oral cavity. The oral mucosa is particularly vulnerable to chemotherapy